Development of Critical Thinking Ability Test using the Rasch Model on Substance Pressure Materials - Eliza Eliza; Tomo Djudin; Erwina Oktavianty (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to produce an instrument to measure students' critical thinking skills on pressure equipment in class VIII SMP. The type of research used is Research and Development (R&D). The type of research used is research and development (R&D). The test instrument developed was in the form of multiple choice based on eight development steps, namely potential and problems, information gathering, product design, product validation, product revision, product testing, product revision, and final product. Validation of the instrument was developed by 3 validators, namely 2 lecturers of Physics Education at FKIP Tanjungpura University and 1 science teacher at the school. The validation given to the validator is in the form of a material validation questionnaire and question validation. The results of material expert validation data obtained 84.72%, validation obtained from content validation with an Aiken index of 0.78, included in the high category and suitable for use. The results of the data analysis of teacher and student response questionnaires obtained 92.60% and 86.26% categorized as very feasible. The results of construct validity using the Rasch model with the application of Winstep 3.73 obtained result 3, which was declared inappropriate because it did not meet the MNSQ, ZSTD, and Pt Measure Corr criteria. The reliability of the Cronbach alpha test value obtained a value of 0.73 with a fairly high category. Regarding the level of difficulty of the item, 4 question items must be discarded because they are included in the very easy and very easy categories. The overall discriminatory power is in the good category with a discriminatory index of 0.40 DP < 70. The results of the study show that out of 30 things, 23 things are appropriate to be used to measure students' critical thinking skills with good-quality items.